MAKNA SAKINAH DALAM SURAT AL-RUM AYAT 21 MENURUT M. QURAISY SYIHAB DALAM TAFSIR AL-MISHBAH DAN RELEVANSINYA DENGAN TUJUAN PERKAWINAN DALAM KOMPILASI HUKUM ISLAM - Kurlianto Pradana Putra; Suprihatin Suprihatin; Oni Wastoni (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2022)
That the Qur’an as a holy book, is believed to be eternal, universal and true. The Qur’an is the main source of Islamic teachings and a way of life for every Muslim. The Qur’an not only contains instructions about the relationship between humans and God, but also regulates human relations with each other (hablum min Allah wa hablum min an-nas), as well as humans with the natural surroundings. Among the issues related to hablum min an-nas discussed in the Qur’an is happiness in marriage as revealed in Surah Al-Rum Verse 21. Happiness in marriage will be expressed through the thoughts of M. Quraish Shihab through the book Tafsir al-Mishbah to reveal the legal aspects. The research was conducted using a library or normative method. While the research data uses secondary data consisting of primary legal materials from the Tafsir al-Misbah book, secondary legal materials such as the Compilation of Islamic Law, and tertiary materials such as dictionaries. Rum verse 21 according to M. Quraish Shihab. The results of this study indicate that in the view of M. Quraish Shihab the word sakinah means calm that is preceded by dynamic turmoil. The expression of sakinah by using the sentence “litaskunu ilaiha” shows the purpose of realizing the tendency to calm down between husband and wife. In the interpretation of al-Mishbah, it shows that there is a tendency that the litaskunu sentence in Surah Al-Rum Verse 21 uses lam ta’lil which contains a tendency or purpose. Applicatively lam ta’lil in the word litaskunu in surah al-Rum verse 21, contains dalalah (guidance) ibarah whose meaning is easy to understand from the text, namely so that there is a tendency to calm down. Thus, in the meaning of sakinah in Surah Al-Rum verse 21, it is found that the tendency of sakinah in a partner must be used as the goal of acting in marriage. This research has relevance to the purpose of marriage in the compilation of Islamic law, as stated in article three of the Compilation of Islamic Law